A revolução e a guerra: discursos da imprensa paulista no movimento constitucionalista de 1932 - Mistrello, Lucas Palma [UNIFESP] (2015)
This paper aims at studying the discourses found in articles, news and manifestoes published by the Press of Sao Paulo State during the event of the 1932 Constitucionalist Revolution, specially those seen in the Jornal das Trincheiras, an ephemeral newspaper created with the objective of distribution throughout the occurrence of the conflict. An attempt was made here in order to understand the claims used by the press to obtain the civilian mobilization in volunteering and war efforts. It is observed two kinds of approach used in the discourses; one, more rational and sober, directed to the commitment to a national and political revolution; and another, more passionate and inflamed, directed to recruit volunteers to a civil war. By this mean, the analysis is divided into two faces ? a war and a revolution ? created by the discourses for the event of July 9th.